Factors associated with suicidal ideation in adults from the Lambayeque Region, Peru, during the COVID-19 pandemic: Factores asociados a ideación suicida en adultos del departamento de Lambayeque-Perú durante la pandemia COVID-19 - Sánchez-Neyra, Almir Carlo (2024)
Objective: Determine the prevalence and factors associated with suicidal ideation in the adult population of the Lambayeque region, Peru, during the COVID-19 pandemic, 2021. Material and methods: Observational, prospective and cross-analytical study; carried out in a sample of 365 adults. Data were collected through Beck's Suicidal Ideation instrument. and a sociodemographic data collection sheet. Results: The sample was characterized by a median age of 26 years (IQR=23-32) and a slight predominance of the female sex (52.2%). The prevalence of suicidal ideation was 28.3%; and was associated with young age (p=0.047), female sex (p<0.001), widowed marital status (p=0.002) and excessive alcohol consumption (p<0.001), and no religion (p <0.001), to the low income (p=0.032) and to the illness (p<0.001) or presence of relatives who died from COVID-19 (p<0.001). Conclusions: There is a high prevalence of suicidal ideation related to the COVID-19 pandemic, so it is suggested to monitor the mental health of the study population.